KOMPARASI METODE SAW, TOPSIS DAN WEIGHTED PRODUCT DALAM PENENTUAN PEMBERIAN KREDIT ANGGOTA KOPERASI KARYAWAN - Muhamad Harun (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Loans to employees can be assessed as a form of support to foster loyalty and work enthusiasm, but on the other hand employee cooperatives entrusted with managing mandatory savings funds must be able to take into account the credit worthiness value without being subjective in order to minimize the possibility of bad credit risk so that the goal long-term member welfare can be achieved and business can run well. Comparisons using the SAW, Topsis and Weighted Product methods in determining the granting of credit to members of cooperatives employees play an important role in providing fast, precise and accurate information to determine credit granting decisions.